APPLICATION OF THERMOMIGRATION FOR TECHNOLOGY OF POWERFUL SEMICONDUCTORS APPLIANCES - Kravchina, V. V.; Polukhin, O. S. (Radio Electronics, Computer Science, Control, 2018)
Contex. The conducted researches allow to improve technological processes of manufacture of semiconductor devices and control of their quality. Objective is to investigate the relief of silicon etching in the area of p + -Si isolation and using of Al-thermigration processes for further develop and improve technology of the power devises. The task of the work is to optimize these technology.Method. The object of the study was the technological features of the processes of forming structures on different routes, differing in the manner of carrying out processes of annealing structures and processes of thermomigration Al. The influence of the annealing time on the features of the microrelief of etching grooves in the region of thermomigration has been studied. Results. The causes of change of breakdown voltage of vertical p-n- junctions formed by thermomigration vs post-migration annealing time and thermomigration process optimization are discussed. On these samples is observed minimal microrelief of the groove etching of various types of conductivity silicon in the area under the insulation of the crystals. Such a minimal microrelief determines the minimum of residual mechanical stresses. The control of changes in the kinetics of etching layers of monocrystalline silicon in the field of thermal migration of aluminum impurities helps in determining the modes of technology for the formation of semiconductor structures with high breakdown electrical voltages. At the same time, two conditions are fulfilled: the first one is the excess of the lateral length of aluminum diffusion over the lateral length of the region of mechanical stresses along the perimeter of the thermo-migration region; and the second, it is a reduction and stabilization of changes in the rate of etching of the thermo-migration layers by minimizing the elasticmechanical, deformation component of the activation energy of the etching process of p+-Si. It is shown that in the manufacture of chips of larger power devices with a larger area and a reverse voltage of up to 2000 V, the optimal variant is the route variant, when the processes of impounding impurities of deep active layers are first carried out, then the processes of thermomigration during the formation of insulation layers. Then there are annealing of isolation and active layers. This combination of annealing processes improves the characteristics of structures. Conclusions. The optimum route, the annealing mode of the structures are determined in the work, and it is shown that monitoring the changes in the etching kinetics of silicon layers in the region of thermal immigration of aluminum impurities helps in determining optimal regimes.